Implementation of rhythmic activities to improve motor movement and social skills - Imas Masripah; Rahmad Khodari; Faisal Rahmat Permana (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2026)
Research Problems: The lack of activities that support optimal physical and social development so that students' motor movements and social skills are less developed. Methods: This study uses a quantitative approach with a One Group Pretest Posttest design. The hypothesis test was carried out using the Paired Sample T-test to determine the effect of the implementation of the Rangku Alu archipelago game on the improvement of students' motor movements and social skills. Results: In the aspect of students' motor skills, the results of the statistical test showed a minimum score of 82 and a maximum score of 100. The significance value is 0.000 < 0.05 and the value is  (36.795 > 2.022). Meanwhile, in the aspect of social skills, in Observation 1, the minimum score is 46.66 to a maximum of 66.66 while in Observation 4, the increase in data is very clear with the minimum score at 80 and the maximum score at 91.66 and the score  (  > 2.022), so there is a significant influence on improving students' motor movement and social skills. Conclusion: Through the game of Rangku Alu which is integrated with the song Manuk Dadali, the activity of jumping, changing positions, and responding to rhythmic movement challenges on the sidelines of bamboo blades becomes effective stimulation in shaping students' motor movements. In addition to improving physical abilities, the game also optimizes students' social skills indicators through fun real-life experiences including improvements in relationships with peers, self-management skills, adherence to rules, and the formation of assertive behaviors. .